Resolving Rohingya Crisis: Obstacles and Prospects - Uddin, Jashim (Advances in Social Sciences Research Journal, 2018)
Despite having geographical proximity and age-old commercial and cultural ties, Bangladesh and Myanmar failed to develop a meaningful relationship. Why? The Rohingya exodus in Bangladesh, albeit, is the key impediment to extend Bangladesh-Myanmar bilateral relationship. Nations have witnessed the crime against humanity in Rakhine for long which brutally killed a lot of Rohingya and forced about 1 million of them to flee from death and enter Bangladesh lead a measurable life. It is not exaggeration to claim that Rohingya, an unorganized ethnic community, are the most persecuted and helpless ethnic minority in today’s world. What’s the future of these ill-fated people is truly uncertain. The suspicious role of Myanmar for a safe repatriation of Rohingya generates doubts and apprehension in the civilized world whether these people can eventually return to their homeland or not. Myanmar has always denied Rohingya as an ethnic minority of Myanmar, In addition, geo-political interests of big powers, military’s engagement in politics in Myanmar, lack of political will from Myanmar, mutual suspicion between Bangladesh and Myanmar ultimately complicate the issue and ultimately block to a durable solution of the Rohingya crisis. Although the neighbors have geo-economic significance and huge potential for mutual cooperation, analyzing the past record and Myanmar’s existing policy, the prospects for a safe repatriation of Rohingya are slim unless the major actors including the UN and big powers in the West, and also China use their carrot and stick policy to induce Myanmar to create a peaceful environment in Rakhine so that Rohingya can return safely and live with dignity.